Comparison measurements of low resistance and high strength on synthesis graphene conductive ink filled epoxy - Salim, Mohd Azli; Ab Wahid, Ameeruz Kamal; Masripan, Nor Azmmi; Md. Saad, Adzni; Photong, Chonlatee (Penerbit UniMAP, 2021)
Stretchable and conductive materials are expected to be widely used for various electronic equipment in the future especially in the field of automotive safety. Flexibility and expandability are the main features of the Stretchable Conductive Ink (SCI) while maintaining the high conductivity levels and can be applied to electronic circuits in vehicles especially for driver health monitoring systems. The experimental work obtained the suitable formulation of the conductive ink based on the resistivity and elasticity values. Five different percentages of samples, 10 wt.% until 30 wt.% with each sample interval represents 5 wt.%. Samples of 20 wt.%, 25 wt.%, and 30 wt.% did not show significant differences in terms of the average volume of resistivity. Filler loading of 25 wt. %of GNP in the filler loading matrix produced the best results for nanomechanical properties. Low resistance and high elasticity of SCI in the vehicle electronic equipment can monitor more effectively the driver's health as SCI can be stretched according to the shape of the human body. It also has good conductivity to measure the movement of the human pulse and muscles.